Production and Promotion Cost Optimization for Corporate Profitability: An Islamic Economic Analysis of PT Mustika Ratu Tbk (2015-2022) - Tusifakh, Nur Azizah; Ekawati, Evi; Zuliansyah, A. (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This study examines the impact of production costs and promotional expenses on corporate profitability through an Islamic economic lens, using PT Mustika Ratu Tbk as a case study from 2015 to 2022. Through a quantitative approach utilizing causal associative analysis, the research analyzes quarterly financial statements (n=32) obtained through purposive sampling. The findings reveal that neither production costs nor promotional expenses significantly influence net profit, either partially or simultaneously. Production costs showed no significant effect (p=0.606 > 0.05), suggesting that standard-compliant production spending does not proportionally correlate with profitability. Similarly, promotional expenses demonstrated no significant impact (p=0.318 > 0.05), indicating that marketing expenditure may be secondary to other factors, such as product quality, in driving profitability. The coefficient of determination (R²=0.072) suggests that these variables account for only 7.2% of profit variation, with 92.8% attributed to external factors. This research contributes to understanding cost management in Islamic business contexts and provides insights for optimizing resource allocation in Indonesia's cosmetics industry. The findings offer practical implications for corporate financial strategy while maintaining alignment with Islamic economic principles.